Compaction quality assessment of cement stabilized gravel using intelligent compaction technology—A case study. (22nd August 2022) - Wang, Ning; Ma, Tao; Chen, Feng; Ma, Yuan
Highlights: A geospatial analysis method is proposed to evaluate the compaction process. The water content significantly affects the correlation between compaction results. Compaction degree and its uniformity do not always increase with roller passes. A novel method for imaging compaction degree and its uniformity is developed. Abstract: As a new compaction quality management system of road construction, the intelligent compaction (IC) technology has shown a great potential for quality control and acceptance (QC/QA) in the compaction of cement stabilized gravel (CSG) subbase. However, before it achieves a high level of technology readiness, there are some challenges to be solved. One of the critical problems is that there is no reliable correlation between IC measurement values (ICMVs) and field test measurements, which is thus focused on. The influence of moisture content on the relationships between ICMVs and density were studied. Two types of ICMVs, roller-integrated stiffness (Kb ) and compaction meter value (CMV), were collected and their correlations with material compactness were established respectively. In addition, it discusses the changing pattern of compaction degree and its uniformity with roller passes. The results show that, moisture content has a significant effect on the correlation between ICMVs and compaction degree of CSG. Compared with CMV, Kb has a higher regression coefficient with the in-situ measurements. Also, it is proven that the compaction degree and uniformity of CSG do not necessarily increase with the development in the number of rolling passes. Finally, this study makes a comprehensive evaluation of the compaction quality of the test section based on the relationships between ICMVs and in-situ test results.